Solid lipid nanoparticles loaded with curcumin: Development and in vitro toxicity against CT26 cells - Ganassin, Rayane; Da Silva, Victor Carlos Mello; Araujo, Victor Hugo Sousa; Tavares, Giulia Rosa; Da Silva, Patrícia Bento; Cáceres-Vélez, Paolin Rocio; Porcel, Joaquin E Martínez; Rodrigues, Mosar Corrêa; Andreozzi, Patrizia; Fernandes, Richard Perosa [UNESP]; Fonseca-Santos, Bruno; Moya, Sergio; et al. (Taylor & Francis, 2022)
Aim: To develop a new curcumin carrier consisting of murumuru butter nanoparticles (SLN-Cs). Methods: A phase-inversion temperature method was used to produce SLN-Cs. The interaction of SLN-Cs with murine colon adenocarcinoma (CT26) cells in vitro was analyzed by confocal microscopy. Results: Stable SLN-Cs with a high curcumin-loading capacity were obtained. The SLN-Cs were more toxic to CT26 than free curcumin. Fluorescence microscopy images showed the SLN-Cs to be taken up by CT26 cells in vitro. Conclusion: These results indicate that SLN-Cs are suitable carriers of curcumin in aqueous media.
Keywords: cancer; colloid; colon adenocarcinoma; drug delivery; murumuru butter